Do vitamins affect the morphophysiology of lettuce in a hydroponic system? - Eduardo P. Vendruscolo; Cássio de C. Seron; Eduardo A. S. Leonel; Sebastião F. de Lima; Suleiman L. Araujo; Murilo B. Martins; Gabriela R. Sant’ Ana; Janaina J. de Oliveira (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Technologies once applied exclusively in conventional systems have maximized gains in hydroponic systems; however, they still need information for proper use. Thus, the study aimed to evaluate the effect of foliar application of thiamine and niacin on growth and gas exchange activities in two lettuce cultivars in an ebb and flow hydroponic system. The completely randomized design (CRD) was used with four treatments and eight replications. The treatments were as follows: T1 - control, T2 - thiamine at a concentration of 200 mg L-1, T3 - niacin at 200 mg L-1, and T4 - thiamine and niacin combined at 100 mg L-1 of each vitamin. Each experimental plot consisted of a lettuce plant. The combined application of thiamine and niacin stood out, increasing the activity of gas exchange of lettuce plants and increasing by about 30% the fresh mass, concerning the control, for both cultivars, followed by the isolated application of niacin. For thiamine, the application alone did not result in significant changes. The vitamins affect the morphophysiology of lettuce, where the use of niacin has the potential for use in hydroponic production systems. Its combined use with thiamine increases this potential, with a synergistic effect between the compounds being verified.